Identification and validation of the role of c-Myc in head and neck squamous cell carcinoma - Zhao, Sufeng; An, Li; Yang, Xudong; Wei, Zheng; Zhang, He; Wang, Yufeng (Frontiers in Oncology, 2022)
Background: Many studies have shown that c-Myc plays a critical role in tumorigenesis. However, the molecular role of c-Myc in head and neck squamous cell carcinoma (HNSC) remains unclear. Methods: Several biological databases, including UALCAN, TIMER2.0, TCGAportal, GEPIA, KM plotter, OncoLnc, LinkedOmics, GSCA, and TCIA, were used to analyze the molecular role of c-Myc in HNSC. The expression levels of c-Myc were validated by real-time PCR (RT–PCR) and Western blot in CAL-27 cells. Results: The expression levels of c-Myc mRNA were significantly increased in HPV-negative HNSC tissues. The c-Myc expression level was correlated with TP53 mutation status. HNSC also showed hypomethylated c-Myc compared with normal tissues. c-Myc was identified as an ominous prognostic factor for HNSC patients and correlated with immune infiltrating levels. Moreover, high c-Myc expression was associated with decreased expression of a series of immune checkpoints, resulting in a dampened immune response. c-Myc potentially mediated RNA transport, RNA polymerase, and RNA degradation. Inhibition of c-Myc expression increased apoptosis of CAL-27 cells. Conclusions: These findings suggest a new mechanism of C-myc in the prognosis of HNSC, implying the potential of C-myc as a therapeutic target for HNSC patients.